PELATIHAN PEMBUATAN TEPUNG UMBI-UMBIAN KEPADA WADAH PEREMPUAN JEMAAT GPM LUMAHPELU, KECAMATAN TANIWEL TIMUR, KABUPATEN SERAM BAGIAN BARAT - Lopulalan, Cynthia G. C.; Mailoa, Meyticorfrida; Tuhumury, Helen C. D.; Moniharapon, Erynola; Sipahelut, Sophie G.; Nendissa, Sandriana J.; Suat, Rahmawati; Lakalay, Lilian; Damayanti, Andini (Universitas Pattimura, 2025)
This community service activity aims to increase the capacity and skills of the Women's Forum of the GPM Lumahpelu Congregation in East Taniwel District, West Seram Regency, in processing local tubers into high-value flour. Tubers such as sweet potatoes, cassava, taro, and taro are abundant in the region, but their utilization is still limited to household consumption. Through this training, participants were introduced to simple tuber flour production technology, including raw material selection, washing, slicing, drying, flouring, and packaging. The training included counseling, hands-on demonstrations, and practical guidance on flour production using simple equipment available in the community. The training was attended by enthusiastic members of the GPM Lumahpelu Congregation's Women's Forum, who participated enthusiastically in every stage of the training. Evaluation of the training showed an 85% increase in participants' knowledge regarding hygienic and marketable flour processing and storage. Furthermore, participants gained an understanding of food diversification through the use of local flour for various processed products such as cakes and snacks. The results of this activity demonstrate that tuber flour production training can improve skills and open up opportunities for small businesses based on local food. This activity contributes to women's economic empowerment, strengthening household food security, and sustainably preserving local food resources.